Evaluating the Type and Number of Errors in Medical Records Documentation in Tehran Ayatollah Taleghani Hospital - Azam Shams; Khalil Alimohammadzadeh; Seyed Mojtaba Hosseini (Shahid Sadoughi University of Medical Sciences, 2018)
Introduction: Recording Medical information in hospital records are in fact documentation of the medical team activities in the hospital. Therefore, correct, accurate, and timely record of patients' information can play a vital role in improving educational, medical, research, legal, and statistical activities. This study aimed to investigate the type and amount of errors in medical records documentation and its effective factors in Ayatollah Taleghani Hospital. Methods: This descriptive-analytic study was cross-sectional. A sample of 330 patients' records in Ayatollah Taleghani Hospital was investigated through a self-made checklist. Data were analyzed by the SPSS software and descriptive and analytical methods. Results: The amount of error in the records showed that, among the examined errors, the lack of record in diagnosis and drug use time in more than 50% of the cases were not accurately recorded. The least error was due to the absence of time and stamp. There was a significant relationship between medical record errors and some demographic characteristics. Conclusion: According to the results and the existence of errors in recording files, hospital doctors and nurses' efforts to promote the documentation of cases were necessary. Rewardingly, some methods, such as initial training of newly arrived residents, encouraging methods, and periodic evaluation of cases can be used.